PAPAN PARTIKEL DARI CAMPURAN LIMBAH ROTAN DAN PENYULINGAN KULIT KAYU GEMOR (Alseodaphne spp) - Cahyana, Budi Tri (Kementerian Perindustrian, 2014)
Utilization of rattan waste and gemor bark (Alseodaphne spp) distillationÂ for particle board had been carried out. The aim of this research was to know physical mechanical particle board from rattan waste mixed with gemor bark distillation. The raw materials used were cut-rattan waste of 2 cm and gemor bark distillation mashed in 16 mesh. The adhesive used were starch and PVAC. Composition variety of the mixture of rattan waste and gemor bark distillation particle were 50%: 50%, 60%: 40%, 70%: 30% and 5% adhesive. The results showed that highest average of modulus of rupture (26,62 kg/cm2) was obtained in 60% : 40% comparison of rattan waste and gemor bark distillation with starch adhesive (a2b1) and the density was 0.75 gr/cm3. The highest average of modulus of elasticity (633,76 kg/cm2) was in composition of 60%: 40% with PVAc adhesive (a2b2) and the density was 0,71 gr/cm3. The highest average of tensile strength (3,15 kg/cm2) was obtained in composition of 60%: 40% with starch adhesive (a2b1) and the density wasÂ 0.75 gr/cm3.Keywords: rattan waste, gemor bark distillation, particle board